ANALYSIS OF PROBLEM-SOLVING SKILLS OF STUDENTS CLASS XI IN TERMS OF SELF-CONFIDENCE - Mumtaz, Nabil Roy; Kusmaryono, Imam; Rusdiantoro, Achmad (Universitas Islam Sultan Agung, 2025)
This study aims to analyse and describe the ability of mathematical problem solving of the students' self-confidence in learning exponent and logarithm functions. This research uses a qualitative approach with a descriptive method. Data collection techniques are based on tests, self-confidence questionnaires, and interviews. The research subjects consisted if six students of class XI B. The results showed based on students with a high level of self-confidence have high problem-solving ability. Students who have a moderate level of self-confidence have a moderate category of problem-solving ability. Meanwhile, the percentage of students with low self-confidence levels has the low category of problem-solving ability. It concludes that there is a linear correlation between self-confidence level and mathematics problem-solving ability of grade XI students on exponent and logarithm functions